Dynamics Between Quantities and Prices in Argentine Dairy Chain: A Structural Cointegration Analysis (2019)
In this work is addresses the dynamics between quantities and prices, at one of the most important economic activities in the Argentine economic system, in order to analyze the relationships between these variables, because they are keys in the knowledge of the sectorial performance. An error correction vector model was used to incorporate the simultaneity existing in the definition of those endogenous variables in a multilevel productive chain context, adding also exogenous information on the supply and demand characteristics of the activity at its different levels was added. To achieve the latter, it was carried out a long and short-term analysis on the dynamics found for all levels of the chain. As a result, it was observed stable short and long-term relationships, in which the wholesale price was one of the most important. In addition, it allowed knowing the internal-external market dynamics as its relationship with the primary level.